Automated Machine Learning implementation framework in the banking sector - Carmona, Pedro Bernardo Resina Baptista Barreiros (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics